Change in Defense Mechanisms and Depression in a Pilot Study of Antidepressive Medications Plus 20 Sessions of Psychotherapy for Recurrent Major Depression. Issue 4 (April 2020) - Perry, J. Christopher; Banon, Elisabeth; Bond, Michael
Abstract : Abstract: Treatment studies of major depression commonly focus on symptoms, leaving aside change in putative psychological risk factors. This pilot study examines the relationship between changes in eight depressive defenses and depressive symptoms. Twelve adults with acute recurrent major depression were given antidepressive medications and randomized to 20 sessions of either cognitive behavioral therapy or dynamic psychotherapy and followed for 1 year. Defenses were assessed using the Defense Mechanism Rating Scales (DMRS) and Defense Style Questionnaire (DSQ) at intake, termination, and 1-year follow-up. Depression improved highly significantly on both the Hamilton Rating Scale for Depression and Beck Depression Inventory, respectively, eight (67%) and nine (75%) patients attained recovery by 1 year. Depressive defenses improved significantly by termination (mean ES = 0.97; 95% confidence interval, 0.30–2.16), but retrogressed somewhat by 1 year. A mean of 12.17% (SD = 10.60) depressive defenses remained; only five subjects (50%) attained normative levels. Although causal relationships were not established, depressive defenses are promising candidates for mediating treatment effects on outcome of major depression.